SPREADING THE USE OF EGNSS (Perner's Contacts, 2016)
This article focuses on spreading the use of European satellite navigation systems in aviation. Development of satellite navigation systems and their applications overcame all obstacles in the last five years and currently is the best and cheapest option in aircraft navigation. The article describes the recent progress in the field of satellite navigation, a new type of approach LPV-200 and its position against ILS approach systems in terms of costs and benefits.